Evaluation of the efficacy and safety of tavaborole topical solution, 5%, in the treatment of onychomycosis of the toenail in adults: a pooled analysis of an 8-week, post-study follow-up from two randomized phase 3 studies. (2nd January 2018) - Gupta, Aditya K.; Hall, Steve; Zane, Lee T.; Lipner, Shari R.; Rich, Phoebe
Abstract: Purpose: The role of topical antifungal agents in the long-term management of toenail onychomycosis is not well established. The current study evaluated durability of clinical benefit of tavaborole topical solution, 5%, for the treatment of toenail onychomycosis. Methods: We conducted a pooled analysis of 8-week, post-study follow-up (PSFU) data from two phase 3, randomized controlled trials in a subset of patients who experienced complete or almost clear nail (CN) at the end of treatment (week 52); 48 weeks of treatment with once-daily tavaborole compared with placebo in adults with distal subungual onychomycosis was evaluated at week 60. Complete cure (completely CN plus negative mycology) of the target great toenail and treatment success (<10% nail involvement plus negative mycology) were evaluated at week 52 versus week 60. Results: Of the 62 patients who completed the PSFU, complete cure was higher in the tavaborole-treated group versus the vehicle control group (28.6% vs. 7.7%). Additionally, treatment success was 53.1% for the tavaborole group versus 23.1% in the vehicle group. Small sample size entering the PSFU limited robust statistical analysis. Conclusion: Tavaborole topical solution, 5%, appears to provide durable clinical benefit, making it an attractive long-term treatment option for dermatophyte-associated onychomycosis of the toenail.